2019
DOI: 10.12659/ajcr.916947
|View full text |Cite
|
Sign up to set email alerts
|

Modified Radical Mastectomy for Male Breast Cancer

Abstract: Patient: Male, 35Final Diagnosis: Male breast cancerSymptoms: Painless breast massMedication: —Clinical Procedure: Modefied radical mastectomySpecialty: SurgeryObjective:Unusual setting of medical careBackground:Cancer of the male breast is a rare malignancy comprising less than 1% of all male cancers. The traditional surgical management for male breast cancer is modified radical mastectomy. Other surgical methods such as breast conserving surgery with or without sentinel lymph node biopsy have been used with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Traditional radical mastectomy requires the entire breast and surrounding tissues to be removed due to the large excision range, which is rarely used in clinical practice [3]. The modified version of radical surgery has gradually developed into a common clinical procedure because of the surgical preservation of the pectoralis muscle and better postoperative appearance [4]. However, for young women, the lack of breasts after radical surgery will greatly impact the patient's self-esteem, affect future marital relationships, breastfeeding, etc., making patients prone to anxiety, depression, low self-esteem, and other negative emotions, affecting the treatment effect [5].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional radical mastectomy requires the entire breast and surrounding tissues to be removed due to the large excision range, which is rarely used in clinical practice [3]. The modified version of radical surgery has gradually developed into a common clinical procedure because of the surgical preservation of the pectoralis muscle and better postoperative appearance [4]. However, for young women, the lack of breasts after radical surgery will greatly impact the patient's self-esteem, affect future marital relationships, breastfeeding, etc., making patients prone to anxiety, depression, low self-esteem, and other negative emotions, affecting the treatment effect [5].…”
Section: Introductionmentioning
confidence: 99%
“…9 The most commonly used standardized procedures for treatment of breast cancer is modified radical mastectomy along with the clearance of axillary lymph nodes. 10,11 However, there are certain complications that are associated with the surgical procedures before and after the surgical management of breast cancer. 12 The commonly observed complications associated with mastectomy in this study were formation of seroma observed in 30 patients.…”
Section: Discussionmentioning
confidence: 99%
“…1970' li yıllara kadar EMK' nde radikal mastektomi uygulanmaktaydı, sonrasında modifiye radikal mastektomi EMK cerrahisinde standart haline gelmiştir. Ancak son dönemde meme koruyucu cerrahi uygulama oranları artmıştır [17]. Yakın tarihli çalışmalarda erkek hastalarda olumlu benlik imajını korumak için meme koruyucu cerrahiye eğilim olduğu ve meme koruyucu cerrahinin olumlu psikososyal sonuçlarla ilişkili olduğu gösterilmiştir [18,19].…”
Section: Discussionunclassified